Evaluation of anesthetic skills acquisition in pre-graduate veterinary students with different grades of anesthetic experience using veterinary simulation exercises - Amitrano, Fernando N.; Quiroz, Lorenzo E.; Jaffe, Ilona R.; Goetz, Nellie G.; Coy, Haverley A.; Keegan, Robert D. (Frontiers in Veterinary Science, 2023)
Background Anesthetic skills are usually learned through continuous supervision by experienced trainers who observe, advise and challenge students. Current educational techniques rely less on live animal training and include the use of simulations and models for teaching and assessment of surgical and anesthetic skills. Objective To evaluate the development of anesthetic skills of veterinary students having different levels of previous experience using simulation. An additional aim was to evaluate the impact of the simulation training on students with no anesthesia experience. Study design Single group periinterventional and postinterventional study. Methods Initial and final anesthesia simulation training recording were obtained from 53 randomly selected veterinary students. Seven faculty members blinded to previous student anesthesia experience reviewed the simulation recording and scored student performance using a rubric, results were recorded and analyzed. Results All students participating in an anesthesia and surgery course reached higher proficiency levels on fundamental anesthesia skills regardless of their previous amount of experience with anesthesia. Simulation based learning positively influenced the final score in veterinary students having no previous anesthesia training, suggesting that it is possible for veterinary students to achieve a level of competence in anesthesia skills with simulation-based training. Main limitations Sample size, group simulation, multiple reviewers bias. Conclusion Students having no experience with clinical anesthesia demonstrated remarkable improvement in their skills, achieving a score that was similar to students having extensive prior clinical anesthesia experience. Despite this clear improvement students having no prior clinical anesthesia experience required more time to complete all anesthesia tasks and may require more training sessions to acquire the speed demonstrated by peers who had significant prior clinical anesthesia experience. Overall, all participants reached a higher proficiency level performing fundamental anesthesia skills at the end of the course.